SCHEMES OF SOLAR HEATING SYSTEMS - F. T. Kholmatov (Galaxy International Interdisciplinary Research Journal, 2022)
Solar heating systems differ from other low-temperature heating systems by the presence of a special element-solar collector, which serves to receive solar energy and convert it into thermal energy.